Factors affecting work life balance among generation Y employees of tobacco companies in Kuala Lumpur - Thevi, Ramasamy (2018)
This study was conducted to find out the factors that affect work life balance among Generation Y employees of tobacco companies and used quantitative method to determine the relationship between independent variables which is personality, family demand and technology and dependent variable being work life balance. Through this study, employers can identify the factors which affect work life balance and they can think about how to minimize the negative impact and promote work life balance among Generation Y employees in order to reduce absenteeism, reduce high turnover and increase employee job performance. On the other hand, employees should understand what affects their work life balance and learn how to management their role accordingly. This study involved 114 respondents from accounting and finance department from tobacco companies. Researcher has distributed 152 sets of questionnaires to respondents but only received 114 complete questionnaires. The questionnaire contains 38 items that have used five point Likert scale. Each hypothesis was tested using Statistics Package for Social Science (SPSS) version 23.0. The obtained data were analysed using descriptive and inferential analysis namely correlation and regression. Four hypotheses were formed to perform the inferential analysis to determine the relationship between independent variables and dependent variables. The results of the study showed that all three factors which is personality, family demand and technology is positively related to work life balance. However, technology is the main contributor towards work life balance among Generation Y employees. Respondents demographic details was also discussed using percentage and frequencies. In nut shell, even though Generation Y employees are labeled as digital generation, work life balance will be affected when their work and non-work responsibilities overlaps due to technology. Various recommendations for further research were also addressed.